Exploring the Concept of the Perfect Human Being in the Quran: An Analysis of Model Education - Farideh Rezaei; Naireh Sadat Saadatmand; Zohreh Taghavi (Iranian Journal of Educational Research)
Objective: A perfect human being is a definitive representation and a reflection of the entirety of God's essence, and attaining this esteemed status is achieved under the auspices of education. The aim of this investigation is to scrutinize the framework of model education founded upon the components derived from the Quran. Methods: This study is qualitative in nature concerning its type, and practical with respect to its objectives, as it endeavors to formulate a paradigm for discerning the elements of an ideal human being as articulated within the verses of the Qur'an. Methodologically, it adopts a descriptive-analytical and inferential approach of a comparative nature. Following extensive theoretical and bibliographic research, coupled with the examination of Quranic exegeses and profound contemplation on the interpretation of the Quran, as well as the categorization of data pertinent to the exemplary human being, a comparative conclusion has been drawn. Results: The outcomes of the research encompass seven distinct attributes, namely: divine description, caliphate, Imam, knowledge, power, servitude, and sincerity, culminating in the identification of ten exemplary attributes that contribute to the formation of a model, which include: Alim, Rahim, Rauf, Sabour, Halim, Sattar, Ghafar, Shakur, Aziz, and Hamid. Conclusions: The insights derived from this investigation possess the potential to enhance the pedagogical literacy of educators engaged in exemplary education.